نموذج مقترح لتعزيز أمن الحواسيب ومعدات الشبكات ضد المخاطر الداخلية والخارجية - Ahmed MohmmedNor Ejail (White Nile Journal for Studies and Research, 2026)
This study presents solutions for computer components problems and communication networks tools and the ways to preserve it from all internal and external threats and risks. The study took great care in concerning the damage of the parts of computer as results of un stability of electrical current in the last period. The study aimed to remind the institutions of the risks and threats which surround the computers system and the important of providing budget to build effective protection safety, determines the weak points in protection system and the ways of reinforce it to be secured from damage and loss of information. The study depended on descriptive and elicitation methods in determine the causes which leads to these problems using the models and Algorithm in designing simple protection steps. The study arrived to important results in designing a model has ability to protect the material components of computer, networks and communication tools and presented the best way in simple protection steps which leads to perform it easily by institutions and individuals. The study recommended of the necessary using of these effective methods in protecting materials, components and directed to choose suitable places to turn on computers carefully with great care especially the main servers to turn on them in more protected places, toughening up, using finger print devices to control the entering, complicate and change the passwords in continuity. The study recommended to use modern secure protection tools especially electrical protection devices like (Fuse, Breaker, UPS Battery) and the system of modern observation Cameras with high accuracy (CCTV), obligates the institutions to applicant these models especially in turn on the locations of Data Center.